Proactive Translatology vis a vis Advertising Messages - Calzada Pérez, María (Meta, 2005)
AbstractMuch good work on Translation Studies (TS) has concentrated on the verbal text. Nevertheless, in our post-modern world, multi-modality is exploited to the maximum, as advertising shows. In turn, hyper-textuality is also a common feature of today’s advertising messages. Furthermore, both multi-modality and hyper-textuality are ideologically designed not only to sell products but to promote entire ways of life. In its second section, the present paper draws on Van Leeuwen (1993), Gastil (1992) and Kress and Van Leeuwen (1998) to approach the notion of multi-modality. It also draws on Askehave and Nielsen (2004) to study hyper-textuality in general and structural/associative links in particular. These theoretical proposals are then applied (in sections 3 and 4) to four translated or translation-related ads on paper and/or on electronic format. Finally, section 5 puts forward a series of conclusions related to the topics under discussion, which are connected to the ideological consequences of the translating (or translation-related) task.